Recent trends in predictive biomarkers for determining malignant potential of oral potentially malignant disorders - Gargi S. Sarode; Sachin C. Sarode; Nikunj Maniyar; Nilesh Sharma; Sujata Yerwadekar; Shankargouda Patil (Frontiers Media S.A., 2019)
Despite of the tremendous advancements in the field of cancer prevention, detection and treatment, the overall prognosis of oral squamous cell carcinoma (OSCC) still remains poor. This can be partly imparted to the lack of early detection of oral potentially malignant disorders (OPMDs), especially those at a higher risk of progression into OSCC. Over years, various specific and non-specific markers have been introduced that could predict the malignant transformation of OPMDs; however detail information on these OPMD markers in a concise manner is lacking. Moreover, their use on daily clinical basis still remains questionable. With continuous research in the field of cytology and genomics, several contemporary biomarkers have been discovered that are not yet foregrounded and proved to be more promising than those used conventionally. Here, in the present paper, we overview several recently concluded predictive biomarkers with special emphasis on their role in molecular pathogenesis of OSCC transformation. These markers can be used for risk assessment of malignant transformation in patients with OPMDs as well as for prophylactic conciliation and fair management of the high-risk OPMD patient group.